Bangla speech recognition using 1D CNN and LSTM with different dimension reduction techniques - Nirjhor, S M Mahsanul Islam; Chowdhury, Mohammad Abidur Rahman; Sabab, Md. Nazmus (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.